2022
DOI: 10.1128/mbio.02463-21
|View full text |Cite
|
Sign up to set email alerts
|

The Histone H1-Like Protein AlgP Facilitates Even Spacing of Polyphosphate Granules in Pseudomonas aeruginosa

Abstract: The mechanisms underpinning polyP’s pleiotropic effects on bacterial starvation physiology remain elusive. This simple polyanion’s lack of protein binding specificity has impeded validation of bona fide polyP-binding proteins.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…NAPs may also modulate the partition of DNA between the surface and the interior, change the properties of the condensates, and provide additional interactions that substitute for and compete with interactions with cations. For example, the histone H1-like protein AlgP in P. aeruginosa , which has a +55 charge at neutral pH, localizes to the granules and alters their consolidation dynamics 26 . Furthermore, our results indicate that other polyvalent cationic species, including other divalent cations, whose concentrations can vary in response to both extracellular and intracellular cues, can likely mediate and tune polyP granule formation, as well as their interactions with DNA and materials properties, and will be an exciting avenue for future investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAPs may also modulate the partition of DNA between the surface and the interior, change the properties of the condensates, and provide additional interactions that substitute for and compete with interactions with cations. For example, the histone H1-like protein AlgP in P. aeruginosa , which has a +55 charge at neutral pH, localizes to the granules and alters their consolidation dynamics 26 . Furthermore, our results indicate that other polyvalent cationic species, including other divalent cations, whose concentrations can vary in response to both extracellular and intracellular cues, can likely mediate and tune polyP granule formation, as well as their interactions with DNA and materials properties, and will be an exciting avenue for future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work also demonstrates that polyphosphate drives heterochromatin formation in E. coli by modulating the DNA-binding affinity of nucleoid associated proteins (NAPs) like Hfq 25 . We previously found that polyP granules in P. aeruginosa are enriched in specific DNA binding proteins, including the histone H1-like protein AlgP 26 . Together, these observations implicate polyP condensates as an important feature of bacterial chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the ultrastructure of the granules where poly-P is accumulated and where the machinery for making poly-P should be associated. Distinct proteome and biochemical analysis have identified several proteins bound to the poly-P granules, such as the histone-like protein AlgP from P. aeruginosa (50) or proteins carrying the positively-charged C onserved H istidine α -helical D omain (CHAD) in Ralstonia eutropha , Magnetospirillum gryphiswaldense and P. putida (51). Diverse Ppk enzymes are also associated with poly-P granules in R. eutropha (52), Caulobacter crescentus (53) or P. aeruginosa (50), but Ppx has not been yet identified in these kind of analyses (50).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Sc10g003170 ( MetRS ) might modulate N accumulation through modulation of extensive protein synthesis, and the direct targets and underlying mechanism need to be further revealed in the future. The transcriptional regulatory protein AlgP is a DNA‐binding protein, that is widely involved in gene expression regulation (Chawla et al., 2022). In the present study, we found that Sc18g015190 ( AlgP ) might modulate P concentration via transcriptional and post‐transcriptional reprogramming in cassava, and the underlying transcriptional modules need to be further investigated.…”
Section: Discussionmentioning
confidence: 99%